Inside Back Cover: The Cysteinome of Protein Kinases as a Target in Drug Development (Angew. Chem. Int. Ed. 16/2018). Issue 16 (9th March 2018) - Chaikuad, Apirat; Koch, Pierre; Laufer, Stefan A.; Knapp, Stefan
Abstract : Covalent and reversible covalent bond formation with cysteine residues located in the vicinity of the ATP binding site in protein kinases has led to inhibitors with high potency and exclusive isoform selectivity and now four approved kinase drugs. As outlined by S. Knapp et al. in their Review onpage 4372, the successful development of these interesting inhibitors requires careful fine tuning of reactivity, precise positioning of the reactive moiety on a suitable ATP mimetic compound and careful characterization of these inhibitors in cells and in vivo.